Dimethyl fumarate titration for the systemic treatment of moderate-to-severe plaque psoriasis - Giovanna Malara; Gabriella Fabbrocini; Caterina Trifirò; Martina Burlando (BioExcel Publishing Ltd, 2021)
Background: Dimethyl fumarate (DMF) is an oral systemic agent approved for the treatment of moderate-to-severe psoriasis vulgaris. It has a favourable tolerability profile, but it is associated with a high incidence of mild and reversible adverse events. The aim of the article is to describe a clinical experience aimed at increasing tolerability. Patients and methods: A group of patients was treated with DMF with a titration schedule, according to clinical practice, although a personalization of the step-up timing was allowed. The highest dose was the minimal effective dose or the maximal tolerated doses. Results: DMF treatment was effective in reducing the disease severity and improving the quality of life. DMF was well tolerated as only mild, mainly gastrointestinal, adverse events occurred in these patients. In addition, the up-titration schedule seemed to provide a reduced incidence of adverse events compared with the fixed dose. Conclusion: Our experience suggested that the recommended up-titration schedule of DMF, adjusted and personalized according to patient needs and physician opinion, provided a relevant clinical benefit and was well tolerated.